Implementasi Program Green School dalam Penguatan Karakter Peduli Lingkungan Peserta Didik - Justin Foera-era Lase; Kerisman Harefa; Dwi Elfi Notalenta Gea; Fitri Yuliani Gulo; Kristiani Zega; Rufina Zagoto; Febri Prasetia Zega; Rivaldo Sastriawan Gulo; Aldi Januari Zai; Kharisman Hulu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
A school environment lacking greenery and vegetation can affect learning comfort and hinder the development of students' environmentally conscious character. These issues were identified at SMP Negeri 3 Sitolu Ori, which faces limitations in ecological spatial arrangement and low student participation in environmental maintenance. This community service initiative aims to create a green and pleasant school environment, foster environmental awareness, and repurpose waste materials into useful items through the implementation of a